Management of Shivering in Post-Spinal Anesthesia Using Warming Blankets and Warm Fluid Therapy - Arina Qona'ah; Novi Enis Rosuliana; I Made Amartha Bratasena; Wahyu Cahyono (Universitas Airlangga, 2019)
Hypothermia is a common and serious complication of spinal surgery and it is associated with many harmful perioperative outcomes. The aim of this study was to compare the effectiveness of warming blankets and warm fluid therapy to manage shivering. A quasi-experiment with a non-equivalent control group was applied as the research design. There were 60 patients involved in the study. The instrument of this study was a warmer fluid modification, a warming blanket and a cotton blanket. The data was analyzed using an applied paired t-test and independent t-test. After 60 minutes of the intervention, the mean and SD of body temperature of the patients receiving warm fluids was 36.71 ± 0.18, a warming blanket was 36.12 ± 0.35, and the control group was 35.76 ± 0.22. The p values were 0,000. Warm fluid therapy and warming blankets are significant in terms of increasing the body temperature of post-spinal anesthesia patients. Warm fluids are more effective than warming blanket. Warming blankets and warm fluid therapy can be used as a way to increase the body temperature of patients with hypothermia.